Immobilization of Coal Fly Ash in Alginate Beads for Adsorption of Fe (III) Ions - Fauzan Irfandy; Husna Muizzati Shabrina; Indriana Lestari; Heni Anggorowati; Perwitasari Perwitasari (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Various industrial, agricultural, household, mining, smelting, and chemical industrial activities can generate waste containing heavy metals such as Fe(III). Fly ash has the potential as an effective adsorbent to capture heavy metals in wastewater. This study aims to immobilize coal fly ash in alginate beads for the adsorption of Fe(III) ions from synthetic waste solution. To test the adsorption capability of fly ash-alginate beads was performed by varying the contact time (1-24 hours), the mass of fly ash-alginate beads (5, 15, 35, 45, and 55 grams), and the initial concentration of Fe (III) ions at 6, 8, and 10 ppm. The determination of the concentration after adsorption was done using a UV-Vis spectrophotometer. The results showed that fly ash-alginate beads were able to remove Fe(III) ions up to 68.60% at a bead mass of 55 g, ion concentration of 10 ppm, and the equilibrium contact time was reached after 5 hours. The analysis results indicated that the adsorption mechanism followed the Freundlich isotherm model due to the heterogeneous surface exhibited.Keywords:Fly ash, Fe (III), Beads, Adsorption, Freundlich